Ethical challenges in paediatric care: Leveraging the Malaysian Child Act 2001 for life-saving decisions – A case report - Velkanthan Muniandy; Lili Husniati Yaacob; Imran Ahmad; Norzarina Ireny Mohd Nazri (Malaysian Family Physician)
Refusal of medical treatment in paediatric case presents significant ethical and legal challenges, particularly when parental decisions conflict with a child’s welfare. We report a case of life-threatening congenital diarrhoea in a neonate where the parents initially refused hospital admission despite extensive counselling. Given the severity of the child’s condition, legal intervention under the Malaysian Child Act 2001 was necessary to ensure prompt medical care. This case underscores the importance of healthcare providers being well-versed in ethical principles and legal frameworks to protect vulnerable patients. Additionally, it highlights the need for clear national guidelines on invoking the Child Act in primary care settings to provide structured decision-making pathways for healthcare professionals. Ultimately, balancing parental autonomy with a child’s best interests is essential in life-threatening conditions, reinforcing the role of legal mechanisms in safeguarding paediatric patients.